The influence of modulators of acetylcholinesterase on the resistance of mice against soman and on the effectiveness of antidotal treatment of soman poisoning in mice - Kassa, Jiří; Korábečný, Jan; Nepovímová, Eugenie; Jun, Daniel (Journal of Applied Biomedicine, 2018)
The potency of one reversible inhibitor of acetylcholinesterase (6-chlorotacrine), one reactivator of acetycholinesterase (K027) and their combination to increase the resistance of mice against soman and the efficacy of antidotal treatment of soman-poisoned mice was evaluated. While 6-chlorotacrine was able to markedly protect mice against acute toxicity of soman and the pharmacological pretreatment with 6-chlorotacrine increased the efficacy of antidotal treatment (the oxime HI-6 in combination with atropine) of soman-poisoned mice more than two times, the bispyridinium oxime K027 did not protect mice from acute toxicity of soman, however, the pharmacological pretreatment with this compound was able to markedly increase the efficacy of antidotal treatment of soman-poisoned mice. On the other hand, the combination of both modulators of acetylcholinesterase did not increase the prophylactic efficacy of 6-chlorotacrine alone. These findings demonstrate that pharmacological pretreatment of somanpoisoned mice can be promising and useful in the case of administration of 6-chlorotacrine while the administration of the oxime K027 did not bring any additional benefit when combined with 6- chlorotacrine.
Keywords: rezistence k insekticidům; antidota; Atropine; oximy; Mice; Antidotes; Insecticide Resistance; myši; Models, Animal; takrin; Tacrine; Oximes; Male; Soman; reaktivátory cholinesterasy; Drug Synergism; kombinovaná farmakoterapie; soman; synergismus léků; mužské pohlaví; cholinesterasové inhibitory; atropin; Cholinesterase Inhibitors; modely u zvířat; Cholinesterase Reactivators; Drug Therapy, Combination